Echo planar imaging with compressed sensitivity encoding (EPICS): Usefulness for head and neck diffusion-weighted MRI. Issue 155 (October 2022) - Yoshida, Naofumi; Nakaura, Takeshi; Morita, Kosuke; Yoneyama, Masami; Tanoue, Shota; Yokota, Yasuhiro; Uetani, Hiroyuki; Nagayama, Yasunori; Kidoh, Masafumi; Azuma, Minako; Hirai, Toshinori
Abstract: Purpose: To evaluate diffusion-weighted imaging (DWI) using echo planar imaging ( EPI ) with compressed SENSE (EPICS) of the head and neck magnetic resonance imaging (MRI). Method: We retrospectively observed 32 patients who underwent head and neck DWI according to either the conventional method (SENSE, reduction factor = 2), fast scanning method (SENSE, reduction factor = 4), or fast scanning method with EPICS (EPICS, reduction factor = 4). For quantitative analysis, contrast-to-noise-ratio (CNR), apparent diffusion coefficient (ADC) values, geometric distortion, and coefficient of variations (CV) were measured and compared. For qualitative analysis, all images were independently and blindly evaluated by two board-certified radiologists. Results: EPICS revealed the higher CNR between all location compared to those of SENSE with reduction factor = 4. Distortion in the anterior-posterior direction was significantly lower on EPICS than on the conventional scan ( p = 0.02). A comparison between the ADC values of the EPICS and conventional scan revealed no significant differences. The CV was significantly lower for EPICS than the conventional scan [DWI: 0.22 (IQR: 0.15–0.30) vs 0.32 (IQR: 0.24–0.40), p = 0.02]. Conclusions: Compressed SENSE combined with the high acceleration factor can improve image quality, homogeneity, and distortion in the head and neck DWI maintaining ADC values and the scan time duration.